TI_GERICHTE 52.2011.102 vom 21. Dezember 2012 , Contributo di miglioria rustici FZE per strada prevalentemente forestale - TI Tribunale d'appello (2012)
Contributo di miglioria rustici FZE per strada prevalentemente forestale